Reduction of febrile neutropenia by using long-acting granulocyte colony-stimulating factors in patients with solid tumors receiving every-2-week chemotherapy - I. B. Kononenko (IP Habib O.N., 2020)
Neutropenia is a common hematological complication of chemotherapy (СT). The number of studies showed that the underperformance of the treatment program due to the development of this type of hematological toxicity could lead to the decrease in therapy efficacy and to the increase in cancer mortality. Infections that occur as a result of prolonged neutropenia are extremely dangerous. The most severe manifestation of grade 4 neutropenia is febrile neutropenia (FN), which can lead to death from severe infections. Such patients should be immediately hospitalized and should receive empirical therapy with broad-spectrum antibiotics. The costs, associated with the hospitalization, due to FN increase total cost of cancer patients treatment. The application of recombinant forms of the natural protein granulocyte colony-stimulating factor (G-CSF) in clinical practice has solved the number of important problems on that front. The clinical studies and common use show that primary and secondary prevention using recombinant G-CSF reduces the risk of FN development and improves the results of the treatment of malignancies. The review provides actual data concerning pharmacological properties, clinical efficacy and reasonable use of G-CSF with prolonged action to prevent FN in patients with solid tumors during 2-week CT cycles. Special attention is paid to CH regimens with the inclusion of 5-fluorouracil, oxaliplatin, irinotecan in the treatment of colorectal cancer (CRC). The use of neoadjuvant treatment in such patients allows to achieve resectability of the tumor and to perform radical surgery. The maintenance of drugs dose intensity throughout the cycle of CT plays an important role in achieving the treatment success. Therefore, the prevention of CT-induced severe neutropenia and FN is especially important in patients who are the candidates for surgical treatment. The results of some studies confirm the necessity of using G-CSF with prolonged action during 2-week CT cycles in patients with CRC.